ENVIRONMENTAL ACCOUNTING FOR WASTE PROCESSING IN SITI AISYAH HOSPITAL LUBUKLINGGAU CITY - Dheo Rimbano (Universitas Gunadarma, 2019)
The concept of Green (environmental) Accounting (Kusumaningtias, 2013; Ratnaningsih et al., 2004; Suparmoko, 2005; Susilo, 2008) namely Environmental Accounting has actually begun to develop since the 1970s in Europe. However, until the mid 1990s, the concept of Environmental Accounting was not much spread. Based on the Constitution of The Republic of Indonesia Number 32 year 2009 concerning Protection and Management of the Environment, Environment is the unity of space with all objects, power, circumstances, and living things, including humans and behavior, which affect nature itself, sustainability and humans and other living things welfare. The focus of this study lies in the application of Environmental Accounting at Siti Aisyah Hospital in Lubuklinggau, based on Government Accounting Standards (SAP) Number 71 year 2010 on Waste Management (Government Accounting, 2011). The problem in this study is to find out whether the application of Environmental Accounting at Siti Aisyah Hospital is in accordance with the Government Standards. The results of this study have shown that Siti Aisyah Hospital in Lubuklinggau has implemented environmental cost accounting. These environmental costs are included in maintenance costs, but the hospital has not presented a specific report on Environmental Accounting in more detail. This hospital has carried out the process of identifying, measuring, recording, presenting, and also disclosing as already explained in Government Accounting Standards No. 71 year 2010, namely presenting environmental costs by including components of environmental costs on general and administrative costs. This hospital has also managed its waste properly and has also incurred environmental costs.